Biomass of invasive plant species as a potential feedstock for bioenergy production. (26th February 2015) - Van Meerbeek, Koenraad; Appels, Lise; Dewil, Raf; Calmeyn, Annelies; Lemmens, Pieter; Muys, Bart; Hermy, Martin
Abstract Invasive alien species (IAS) are one of the most important drivers of species loss. A series of recent (inter)national policies and guidelines however did not prevent new introductions and further spread of non‐indigenous species. But instead of considering invasive plant species as a burden, the biomass production of IAS can be considered and used as an ecosystem service. To assess the possibilities for bioenergy production of four invasive alien plant species in Europe, Fallopia japonica, Heracleum mantegazzianum, Impatiens glandulifera and Solidago gigantea, we determined their biomass production, gross calorific value and biogas yield. The viability of the propagules after digestion was also tested to assess the dispersal risk related to the bioenergy chain. Fallopia japonica and S. gigantea achieved a high annual biomass yield of 8.6 ton DM per hectare. Impatiens glandulifera and H. mantegazzianum had a lower biomass production (5.8 and 6.0 ton DM ha−1). Without extra inputs or agronomic optimization of the crops, the anaerobic digestion of the studied invasive plant species achieved comparable energy outputs per hectare (28–88 GJ ha−1) as some of the current bioenergy systems. All propagules lost their viability after digestion. The risk of further invasion is thus minimized during the digestion process. However, caution during harvest and transport is required to prevent the spread of new propagules. The energetic valorization of the biomass of IAS can create an economic incentive for habitat restoration of invaded sites and offers the opportunity to reconcile the restoration of the invaded habitats with renewable energy goals. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd